2016
DOI: 10.3346/jkms.2016.31.5.790
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Restless Legs Syndrome and Urticaria?

Abstract: Restless legs syndrome (RLS) is a disease characterized by the urge to move the legs and sleep disturbances. Similarly, chronic spontaneous urticaria (CSU) is a dermatological disease characterized by pruritus and sleep disorders. In this study, we aimed to determine the prevalence and severity of RLS in patients with chronic spontaneous urticaria (CSU) and to compare the quality of sleep of patients with and without RLS in the CSU group using the Pittsburgh Sleep Quality Index. A total of 130 patients with CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Bashir et al [36]Cohort study3 CU patientsNo 20. Tuna et al [35]Case–control130 CU patients100 individualsV. Case reports–case series—psychiatric interventions in CU patients 21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bashir et al [36]Cohort study3 CU patientsNo 20. Tuna et al [35]Case–control130 CU patients100 individualsV. Case reports–case series—psychiatric interventions in CU patients 21.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in 2016 Tuna et al [35 ] included 130 patients with CU and 100 healthy controls in a study that aimed to determine the prevalence and severity of restless leg syndrome (RLS) and to compare the quality of sleep of CU patients with and without RLS. The prevalence (23.8%) of RLS in the CU group was significantly higher than the control group (12%).…”
Section: Resultsmentioning
confidence: 99%
“…[23,32] In atopic dermatitis patients, RLS was found to be more frequent and correlated with the disease severity compared with psoriasis and control groups. [32] In another study, Tuna et al [23] showed that frequencies of RLS and sleep disturbances were higher in patients with chronic urticaria than the control group. Authors claimed that RLS and urticaria might share a common etiology and urticaria might trigger and worsen RLS.…”
Section: Discussionmentioning
confidence: 97%
“…A power analysis by Minitab 17 Statistical Software (Minitab, Ltd., Coventry, United Kingdom) according to the results of Tuna et al [23] revealed that 117 patients would be required in each group to detect significant differences with a power of 90% and a level of significance of α=0.05.…”
Section: Discussionmentioning
confidence: 99%